KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 1 TAMBUSAI KABUPATEN ROKAN HULU - Nurhikmah Nurhikmah; Nursal Hakim; Auzar Auzar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: this study examines the ability of writing text Exposition grade X SMA Negeri 1 Tambusai Rokan Hulu. This research aims to know and describe the ability to write text Exposition grade X SMA Negeri 1 Tambusai Rokan Hulu. This research is descriptive-quantitative research. This research data is data the results of executed tests writing skills text Exposition grade X SMA Negeri 1 Tambusai Rokan Hulu. Instruments in the research is written test-shaped shaped essay has three provisions reserved about the ability of writing text Exposition grade X SMA Negeri 1 Tambusai Rokan Hulu. Data collection is carried out by an engineering test. The population in this study as many as 80 students with samples of as much as 67 students. The data were analyzed by descriptive method quantitative Test Chi Square through a sample. The results of this research as seen from the test results the ability write text Exposition grade 80,55Key Words: Ability, writing, text Exposition.